2023
DOI: 10.1108/jepp-03-2023-0021
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship skills: do all dimensions of skills matter for sustainable business start-up?

Anthony Tibaingana,
Kasimu Sendawula,
Faisal Buyinza
et al.

Abstract: PurposeThe purpose of this study is to establish whether all the dimensions of entrepreneurship skills matter for sustainable business start-up among the youths, using evidence from a developing economy.Design/methodology/approachThis was cross-sectional study which utilized a quantitative approach. Data were collected using a self-administered questionnaire from 254 youths who undertook skills training at the various government-supported business skills training centers in the Greater Kampala Metropolitan Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…It is premised on the foundational elements that both skills and financial knowledge are imperative for promoting female employment or reducing female unemployment. Moreover, in the long term, such policies enhance female managerial confidence as well as female opportunities of finding white collar jobs (Ojong et al, 2021;Moyo and Sibindi, 2022;Tibaingana et al, 2024). The positioning of the study also builds on an identified gap in the extant scholarly literature on the subject.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is premised on the foundational elements that both skills and financial knowledge are imperative for promoting female employment or reducing female unemployment. Moreover, in the long term, such policies enhance female managerial confidence as well as female opportunities of finding white collar jobs (Ojong et al, 2021;Moyo and Sibindi, 2022;Tibaingana et al, 2024). The positioning of the study also builds on an identified gap in the extant scholarly literature on the subject.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, in the long term, such policies enhance female managerial confidence as well as female opportunities of finding white collar jobs (Ojong et al. , 2021; Moyo and Sibindi, 2022; Tibaingana et al ., 2024). The positioning of the study also builds on an identified gap in the extant scholarly literature on the subject.…”
Section: Introductionmentioning
confidence: 99%